2018
DOI: 10.21272/mmi.2018.4-31
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in assessing the efficiency of the instruments for the national economy de-shadowing: the state management aspect

Abstract: The article deals with the development of the methodology for improving the state policy of the national economy de-shadowing. It generalizes arguments and counterarguments within the framework of scientific discussion on the main instruments for the national economy de-shadowing. It has been established that tax instruments used for the state influence on the shadow economy allowed achieving a complex effect in all spheres of public life. The purpose of the article is to form an innovative methodology for ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…It has also been found that increased controls on corruption and increased political stability led to a reduction in the number of fraud cases in all sectors of the national economy. Also, the hypothesis regarding a relationship between the effectiveness of governance in the country and inclusive development has been empirically confirmed (Chou, 2018) as well as the growth of corruption under conditions of the shadow economy (Levchenko et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 86%
“…It has also been found that increased controls on corruption and increased political stability led to a reduction in the number of fraud cases in all sectors of the national economy. Also, the hypothesis regarding a relationship between the effectiveness of governance in the country and inclusive development has been empirically confirmed (Chou, 2018) as well as the growth of corruption under conditions of the shadow economy (Levchenko et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 86%
“…З точки зору детінізації та підвищення економічної стабільності національної економіки дане питання досліджували М.А. Субе та А. Бойко [6], Л. Сінєвічене, О. Шкарупа та Л. Сисоєва [7], Т. Кобзієва і Т. Шлапко [8], М. Паліенко та О. Люльов [9]. З боку оподаткування підприємств -Г. Яровенко, Т. Басенко [10], Д. Марченко [11] та О. Люльова [12].…”
Section: економіка і управління підприємствамиunclassified
“…As for the state of the Ukrainian banking sector, according to a study within the USAID Project «Financial Sector Transformation» (Ukrainian Financial Sector Transformation, 2019), Ukrainian banks are accepting digital transformation not as an opportunity but as like a «parallel world». And as a result, Ukrainian banks currently have a low level of participation in fintech companies' capital, members of the bank's board have limited experience in the fintech industry (Levchenko et al, 2018;Vasylieva et al, 2017). Moreover, only 50% of banks have a digital strategy.…”
mentioning
confidence: 99%